Supplier evaluation: a comparison of the approach of czech and german industrial companies - Benediktová, Dagmar; Žižka, Miroslav (Univerzita Pardubice, 2018)
The present article deals with supplier evaluation in Czech and German companies. It addresses the question of whether there are differences in evaluation criteria and methods between Czech and German companies. The article consists of three interconnected parts. The first part presents the results of a literature review that focused on the current trends in supplier evaluation. The subsequent part describes the research methodology. The research was conducted through a questionnaire survey of a sample of 180 Czech and 70 German companies operating in the automotive and related industries. The next part presents the results of the research. The research results have shown that the completeness and timeliness of deliveries is the most important criterion for companies in both countries. Compared to German companies, Czech companies put more emphasis on the price level, the openness of calculations and the supplier’s communication. German companies attach greater importance to quality, indemnity insurance and soft criteria such as an ethical approach. In terms of evaluation methods, it can be concluded that companies in both countries apply rather simpler approaches. In both countries, the same three evaluation methods are most commonly used – scoring model, ABC method and point evaluation.
Keywords: supplier evaluation; evaluation criteria; evaluation methods; automotive industry; scoring model; L23; L62